IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE ON MSMes IN INDONESIA AND USA - Asfufi Nanang; Wike Pratiwi (Accounting Journal of Ibrahimy (AJI), 2024)
ABSTRAK Good corporate governance (GCG) is a key strategy to ensure the openness, accountability, and efficiency of micro, small, and medium-sized enterprises (MSMEs) in the USA and Indonesia. This study's objective is to ascertain the extent to which research is pertinent to the implementation of GCG in MSMEs. The study employs a descriptive qualitative method for this purpose. The research uses a library research methodology. The results of the study have shown that there are several key indicators that can be used to evaluate and improve GCG practices in these companies. The USA has placed a strong emphasis on competence-oriented governance and design, with Functional background and IT proficiency are necessary in the boardroom to comprehend how IT affects business operations and strategic goals. The findings also emphasize the significance of independence, justice, and accountability as critical metrics for assessing and enhancing GCG practice in these businesses.